Increased Anxiety After Stimulation of the Right Inferior Parietal Lobe and the Left Orbitofrontal Cortex - Grieder, Matthias; Homan, Philipp; Federspiel, Andrea; Kiefer, Claus; Hasler, Gregor (Frontiers in Psychiatry, 2020)
Sustained anxiety is a key symptom of anxiety disorders and may be associated with neural activation in the right inferior parietal lobe (rIPL), particularly under unpredictable threat. This finding suggests a moderating role of the rIPL in sustained anxiety, which we tested in the current study. We applied cathodal or sham transcranial direct current stimulation (tDCS) to the rIPL as a symptom provocation method in 22 healthy participants in a randomized, double-blind, crossover study, prior to two recordings of cerebral blood flow (CBF). In between, we applied a threat-of-shock paradigm with three conditions: unpredictable (U), predictable (P), or no electric shocks (N). We hypothesized increased anxiety under U, but not under P or N. Furthermore, we expected reduced cerebral blood flow (CBF) in the rIPL after tDCS compared to sham. As predicted, anxiety was higher in the U than the P and N conditions, and active tDCS augmented this effect. While tDCS did not alter CBF in the rIPL, it did attenuate the observed increase in brain regions that typically increase activation as a response to anxiety. These findings suggest that the rIPL moderates sustained anxiety as a gateway to brain regions crucial in anxiety. Alternatively, anodal tDCS over the left orbitofrontal cortex (lOFC) may have increased anxiety through disruption of OFC-amygdala interactions.